2019
DOI: 10.1038/s41598-019-46214-8
|View full text |Cite
|
Sign up to set email alerts
|

Theta oscillations show impaired interference detection in older adults during selective memory retrieval

Abstract: Seemingly effortless tasks, such as recognizing faces and retrieving names, become harder as we age. Such difficulties may be due to the competition generated in memory by irrelevant information that comes to mind when trying to recall a specific face or name. It is unknown, however, whether age-related struggles in retrieving these representations stem from an inability to detect competition in the first place, or from being unable to suppress competing information once interference is detected. To investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Similarly, in RIF studies, selective retrieval practice robustly increases midline-frontal theta power more than does repeated study of the same items (Staudigl et al 2010) or retrieval practice without competitors (Ferreira et al 2014. Critically, paralleling conflict reduction benefits in fMRI, Staudigl et al (2010) found that midline-frontal theta power declined over retrieval practice blocks (see also Ferreira et al 2019), with steeper declines predicting greater RIF. These effects were source-localized to the ACC.…”
Section: Inhibition Of Competing Memories During Selective Retrievalmentioning
confidence: 82%
“…Similarly, in RIF studies, selective retrieval practice robustly increases midline-frontal theta power more than does repeated study of the same items (Staudigl et al 2010) or retrieval practice without competitors (Ferreira et al 2014. Critically, paralleling conflict reduction benefits in fMRI, Staudigl et al (2010) found that midline-frontal theta power declined over retrieval practice blocks (see also Ferreira et al 2019), with steeper declines predicting greater RIF. These effects were source-localized to the ACC.…”
Section: Inhibition Of Competing Memories During Selective Retrievalmentioning
confidence: 82%
“…It has been proposed that the attention-related prefrontal cortex function is altered with aging, leading to a decline in inhibitory control (Chao & Knight, 1997; West, 1996; but see e.g., Kramer, Humphrey, Larish, & Logan, 1994). For example, research has shown less theta power increase in older adults compared to younger adults during selective memory retrieval, suggesting the elderly being less capable of detecting memory interference (Ferreira et al, 2019). Nevertheless, the prolonged naming times instead of incorrect naming responses in most of the trials suggest that our older participants were still able to inhibit the irrelevant information and resolve the competition between the streams of processing the picture and the distractor.…”
Section: Discussionmentioning
confidence: 99%
“…during retrieval practice of the names of famous people from different categories show a modulation at prefrontal sites that is reduced in older people (Ferreira et al, 2019). This modulation indicates that the process involved in name retrieval in the presence of competition is also the result of a control mechanism that depends on the normal functioning of the prefrontal cortex, which is impaired in older people.…”
Section: Analogical Reasoningmentioning
confidence: 94%
“…Therefore, a relevant question is whether personal representations are as vulnerable to interference as object representations are (Brédart, 2017;Marful et al, 2014), and whether they are also the target of inhibitory control. Indeed, experiments have demonstrated that selective retrieval can render the names of famous people less accessible for retrieval, probably as a result of inhibition (Marful et al, 2015;Ferreira et al, 2019; see Fig. 2b for the procedure from Ferreira et al, 2014).…”
Section: Reduced Access To Personal Informationmentioning
confidence: 99%